Travel behaviour of the elderly in planned and unplanned communities of Lagos Metropolis, Nigeria / Wale Alade and Abubakar Olaseni. - Alade, Wale; Olaseni, Abubakar (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
Interests in the study of travel behaviour of the elderly have been growing in the last two decades and many of the works done are concentrated in the global north. Evidence from literature reveals that most of these studies focus more on the impact of individual and household socioeconomic attributes, urban form, travel attributes, and policy factors on the travel behaviour of the elderly, but less on the influence of neighbourhood planning. This paper examined the travel behaviour of old people in Festac town (planned) and Ketu (unplanned) community of Lagos metropolis, southwest Nigeria with a view to determining the influence of neighbourhood planning on travel pattern. The two neighbourhoods were carefully and purposively selected for collection of socio-economic and travel data through structured questionnaire that was administered on 155 randomly selected elderly respondents. The study revealed significant differences and some similarities in respondents’ socio-economic and travel characteristics. Respondents from the planned community have a higher daily mean trip rate and mean trip time than those in unplanned community. Residents of planned community also undertake higher work and social trips and rely on automobile more than those in unplanned community. Apart from the fact that the majority of respondents travel more during the off-peak period, frequent road congestion was reported as the top mobility challenge among respondents in the two neighbourhoods. The study concluded that neighbourhood planning affects travel behaviour and recommended a walkable neighbourhood concept and promotion of elderly friendly public transport system for the study area.